PENGARUH SOSIALISASI, MOTIVASI, DAN PEMAHAMAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK (STUDI PADA PENGUSAHA KENA PAJAK DI KANTOR PELAYANAN PAJAK PRATAMA MALANG UTARA) - Widiastuti, Diani (Jurnal Mahasiswa Perpajakan, 2014)
This research aims to analyze and explain the influence effect of socialization, motivation, and taxpayer understanding toward taxpayer compliance. This study occurred form the effort that done by Directorate General Taxes wich is conducting the reformation of administrative system in Value Added Tax (VAT). That reformation is tagged by rising regulation in PER-10/PJ/2013 and PER-11/PJ/2013, wich is started on June 2013 that the responsibility to collect and report monthly tax return must be used e-SPT. This research used explanatory research method wich is showed the casual relation between the variables by hypothesis tested. The population of this research is amounted to 1.051 taxpayer that sample determined by using slovin formula wich is amounted to 100 taxpayer. Sample is taken by using simple random sampling technique and data collection method is collected by speading questionnaire. Analysis used multiple linear regression. Based on the result of this analysis is known that socialization variable and taxpayer understanding has a positively and significantly influence toward taxpayer compliance, meanwhile motivation variabel has positively influence unfortunately it hasn’t significantly influence toward taxpayer compliance. Keywords: Socialization, Motivation, Taxpayer Understanding, and Taxpayer Compliance